Kemenarikan dan Konsep Pengembangan Indiana Camp Sebagai Wisata Adventure di Kabupaten Bandung Barat - Resti Winda Fitriani; Rieke Sri Rizki Asti Karini (Manajemen dan Pariwisata, 2022)
Adventure tourism is a type of tourism in the category of special interest tourism. This type has an exclusive impression because it tends to be attracted by certain people or groups who have an interest, because it tends to have a challenging nature and high risk. One of the tourist destinations in West Bandung Regency is Indiana Camp. This destination has the theme of extreme tourism and adventure with the characteristics of cliff heights and Citatah Karst Limestone Mountain. The problem taken is the attractiveness of attractions and the concept of development in Indiana Camp as adventure-based tourism. The method used is descriptive qualitative. Data obtained from primary and secondary data by observation, interviews, documentation, literature, triangulation and questionnaires. The results showed that the aspects of learning, rewarding, enriching and adventure felt by tourists who visited in the category of adventure tourism. Types of attractions and activities are stated in the Soft Adventure category, that attraction activities at Indiana Camp are dangerous, challenging, but fun. Aspects of accessibility to Indiana Camp is not good. Aspects of the facilities available are quite good. Aspects of zoning division already exist and are well implemented. Aspects of circulation route planning are equipped with relevant information. The interpretation program aspect has been implemented. The aspect of building facilities that this destination uses environmentally friendly methods and materials. Aspects of attraction and development of adventure-based tourist attraction are included in the category of adventure-based special interest tourism, because the nature of the attraction is dangerous, challenging, but fun. Based on these results, it can be concluded that the tourist attraction of Indiana Camp is included in the category of adventure tourism.